Microscopic approach to the quantized light-matter interaction in semiconductor nanostructures: Complex coupled dynamics of excitons, biexcitons, and photons - Rose, Hendrik; Schumacher, Stefan; Meier, Torsten (Physical Review B)

Microscopic simulations of the dynamics of excitonic many-body correlations coupled to quantum light - Rose, Hendrik; Sharapova, Polina R.; Meier, Torsten (Ultrafast Phenomena and Nanophotonics XXVIII)

Spin-Dependent Exciton–Exciton Interactions in a Mixed Lead Halide Perovskite Crystal - Grisard, Stefan; Trifonov, Artur V.; Hahn, Thilo; Kuhn, Tilmann; Hordiichuk, Oleh; Kovalenko, Maksym V.; Yakovlev, Dmitri R.; Bayer, Manfred; Akimov, Ilya A. (ACS Photonics)

Theoretical analysis of four-wave mixing on semiconductor quantum dot ensembles with quantum light - Rose, Hendrik; Grisard, Stefan; Trifonov, Artur V.; Reichhardt, Rilana; Reichelt, Matthias; Bayer, Manfred; Akimov, Ilya A.; Meier, Torsten
Dataset of the publication "Theoretical analysis of four-wave mixing on semiconductor quantum dot ensembles with quantum light" H. Rose, S. Grisard, A. V. Trifonov, R. Reichhardt, M. Reichelt, M. Bayer, I. A. Akimov, and T. Meier, Proc. SPIE 12419, Ultrafast Phenomena and Nanophotonics XXVII, 124190H (2023). ( https://doi.org/10.1117/12.2647700 ). The zip file includes the data on which the plots shown in figures 1 and 2 are based.

Temporal Sorting of Optical Multiwave-Mixing Processes in Semiconductor Quantum Dots - Grisard, Stefan; Trifonov, Artur V.; Rose, Hendrik; Reichhardt, Rilana; Reichelt, Matthias; Schneider, Christian; Kamp, Martin; Höfling, Sven; Bayer, Manfred; Meier, Torsten; Akimov, Ilya A. (ACS Photonics)

Quantum-optical excitations of semiconductor nanostructures in a microcavity using a two-band model and a single-mode quantum field - Rose, Hendrik; Vasil'ev, A. N.; Tikhonova, O. V.; Meier, Torsten; Sharapova, Polina (Physical Review A)

Temporal sorting of optical multi-wave-mixing processes in semiconductor quantum dots - Meier, Torsten; Grisard, S.; Trifonov, A.V.; Rose, Hendrik; Reichhardt, R.; Reichelt, Matthias; Schneider, C.; Kamp, M.; Höfling, S.; Bayer, M.; Akimov, I.A (arxiv:2302.02480)

Theoretical analysis of four-wave mixing on semiconductor quantum dot ensembles with quantum light - Rose, Hendrik; Grisard, S.; Trifonov, A. V.; Reichhardt, R.; Reichelt, Matthias; Bayer, M.; Akimov, I. A.; Meier, Torsten (Ultrafast Phenomena and Nanophotonics XXVII)
The nonlinear optical response of an ensemble of semiconductor quantum dots is analyzed by wave-mixing processes, where we focus on four-wave mixing with two incident pulses. Wave-mixing experiments are often described with semiclassical models, where the light is modeled classically and the material quantum mechanically. Here, however, we use a fully quantized model, where the light is given by a quantum state of light. Quantum light involves more degrees of freedom than classical light as e.g., its photon statistics and quantum correlations, which is a promising resource for quantum devices, such as quantum memories. The light-matter interaction is treated with a Jaynes-Cummings type model and the quantum field is given by a single mode since the quantum dots are embedded in a microcavity. We present numerical simulations of the four-wave-mixing response of a homogeneous system for pulse sequences and find a significant dependence of the result on the photon statistics of the incident pulses. The model constitutes a problem with a large state space which arises from the frequency distribution of the transition energies of the inhomogeneously broadened quantum dot ensemble that is coupled with a quantum light mode. Here we approximate the dynamics by summing over individual quantum dot-microcavity systems. Photon echoes arising from the excitation with different quantum states of light are simulated and compared.

Long-Lived Exciton Coherence in Mixed-Halide Perovskite Crystals - Grisard, Stefan; Trifonov, Artur V.; Solovev, Ivan A.; Yakovlev, Dmitri R.; Hordiichuk, Oleh; Kovalenko, Maksym V.; Bayer, Manfred; Akimov, Ilya A. (Nano Letters)

Clinching of Aluminum Materials – Methods for the Continuous Characterization of Process, Microstructure and Properties - Kupfer, Robert; Köhler, Daniel; Römisch, David; Wituschek, Simon; Ewenz, Lars; Kalich, Jan; Weiß, Deborah; Sadeghian, Behdad; Busch, Matthias; Krüger, Jan; Neuser, Moritz; Grydin, Olexandr; et al. (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Coherent contributions to population dynamics in a semiconductor microcavity - Paul, J.; Rose, Hendrik; Swagel, E.; Meier, Torsten; Wahlstrand, J. K.; Bristow, A. D. (Physical Review B)

Low-field onset of Wannier-Stark localization in a polycrystalline hybrid organic inorganic perovskite - Berghoff, Daniel; Bühler, Johannes; Bonn, Mischa; Leitenstorfer, Alfred; Meier, Torsten; Kim, Heejae (Nature Communications)
Abstract Methylammonium lead iodide perovskite (MAPbI 3 ) is renowned for an impressive power conversion efficiency rise and cost-effective fabrication for photovoltaics. In this work, we demonstrate that polycrystalline MAPbI 3 s undergo drastic changes in optical properties at moderate field strengths with an ultrafast response time, via transient Wannier Stark localization. The distinct band structure of this material - the large lattice periodicity, the narrow electronic energy bandwidths, and the coincidence of these two along the same high-symmetry direction – enables relatively weak fields to bring this material into the Wannier Stark regime. Its polycrystalline nature is not detrimental to the optical switching performance of the material, since the least dispersive direction of the band structure dominates the contribution to the optical response, which favors low-cost fabrication. Together with the outstanding photophysical properties of MAPbI 3 , this finding highlights the great potential of this material in ultrafast light modulation and novel photonic applications.
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

Controlling the emission time of photon echoes by optical freezing of exciton dephasing and rephasing in quantum-dot ensembles - Reichelt, Matthias; Rose, Hendrik; Kosarev, Alexander N.; Poltavtsev, Sergey V.; Bayer, Manfred; Akimov, Ilya A.; Schneider, Christian; Kamp, Martin; Höfling, Sven; Meier, Torsten (Ultrafast Phenomena and Nanophotonics XXV)

Accurate photon echo timing by optical freezing of exciton dephasing and rephasing in quantum dots - Kosarev, Alexander N.; Rose, Hendrik; Poltavtsev, Sergey V.; Reichelt, Matthias; Schneider, Christian; Kamp, Martin; Höfling, Sven; Bayer, Manfred; Meier, Torsten; Akimov, Ilya A. (Communications Physics)
Abstract Semiconductor quantum dots are excellent candidates for ultrafast coherent manipulation of qubits by laser pulses on picosecond timescales or even faster. In inhomogeneous ensembles a macroscopic optical polarization decays rapidly due to dephasing, which, however, is reversible in photon echoes carrying complete information about the coherent ensemble dynamics. Control of the echo emission time is mandatory for applications. Here, we propose a concept to reach this goal. In a two-pulse photon echo sequence, we apply an additional resonant control pulse with multiple of 2 π area. Depending on its arrival time, the control slows down dephasing or rephasing of the exciton ensemble during its action. We demonstrate for self-assembled (In,Ga)As quantum dots that the photon echo emission time can be retarded or advanced by up to 5 ps relative to its nominal appearance time without control. This versatile protocol may be used to obtain significantly longer temporal shifts for suitably tailored control pulses.

Strongly nonresonant four-wave mixing in semiconductors - Hannes, W.-R.; Trautmann, Alexander; Stein, M.; Schäfer, F.; Koch, M.; Meier, Torsten (Physical Review B)

Spatially asymmetric transients of propagating exciton-polariton modes in a planar CdZnTe/CdMgTe guiding structure - Vondran, J.; Spitzer, F.; Bayer, M.; Akimov, I. A.; Trautmann, Alexander; Reichelt, Matthias; Meier, Cedrik; Weber, N.; Meier, Torsten; André, R.; Mariette, H. (Physical Review B)

Spatially asymmetric transients of propagating exciton-polariton modes in a planar CdZnTe/CdMgTe guiding structure - Vondran, J.; Spitzer, F.; Bayer, M.; Akimov, I. A.; Trautmann, Alexander; Reichelt, Matthias; Meier, Cedrik; Weber, N.; Meier, Torsten; André, R.; Mariette, H. (Physical Review B)

Signatures of transient Wannier-Stark localization in bulk gallium arsenide - Schmidt, C.; Bühler, J.; Heinrich, A.-C.; Allerbeck, J.; Podzimski, R.; Berghoff, D.; Meier, Torsten; Schmidt, Wolf Gero; Reichl, C.; Wegscheider, W.; Brida, D.; Leitenstorfer, A. (Nature Communications)

Signatures of transient Wannier-Stark localization in bulk gallium arsenide - Schmidt, Claudia; Bühler, J.; Heinrich, A.-C.; Allerbeck, J.; Podzimski, R.; Berghoff, Daniel; Meier, Torsten; Schmidt, Wolf Gero; Reichl, C.; Wegscheider, W.; Brida, D.; Leitenstorfer, A. (Nature Communications)

Coherent optical spectroscopy of charged exciton complexes in semiconductor nanostructures - Akimov, Ilya; Poltavtsev, Sergey V.; Salewski, Matthias; Yugova, Irina A.; Karczewski, Grzegorz; Wojtowicz, Tomasz; Maciej, Wiater; Reichelt, Matthias; Meier, Torsten; Yakovlev, Dmitri; Bayer, Manfred (Ultrafast Phenomena and Nanophotonics XXII)